2022
DOI: 10.3390/ma15030782
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Addition of Hazelnut or Walnut Flour on the Rheological Characteristics of Wheat Dough

Abstract: The aim of this study was to evaluate the effect of the addition of hazelnut or walnut flour on the rheological properties of flour and wheat dough (WD). The research material was a system in which wheat flour was replaced with flour based on hazelnuts (HF) or walnuts (WF), i.e., nut flour, in the amounts of 5%, 10% and 15% (WDH, WDW). As a part of the research methodology, we analysed the wet gluten content, and farinographic and extensographic analyses of the dough were performed. Sweep frequency, creep and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 16 publications
(52 reference statements)
4
23
2
Order By: Relevance
“…Based on published reports, dough stability parameters decreased while the mixing tolerance index increased with increasing amounts of addition in the mixes. This hypothesis is also supported by other authors [61,80,81]. The reduction of hydration capacity could be due to the fact that the addition of nut constituents could disrupt the wheat glutenstarch network, competing with wheat flour proteins for water, and then decreasing its stability.…”
Section: Testing the Rheological Character Of The Semi-finished Produ...supporting
confidence: 64%
See 2 more Smart Citations
“…Based on published reports, dough stability parameters decreased while the mixing tolerance index increased with increasing amounts of addition in the mixes. This hypothesis is also supported by other authors [61,80,81]. The reduction of hydration capacity could be due to the fact that the addition of nut constituents could disrupt the wheat glutenstarch network, competing with wheat flour proteins for water, and then decreasing its stability.…”
Section: Testing the Rheological Character Of The Semi-finished Produ...supporting
confidence: 64%
“…In addition, other research, by Pycia et al [80] was characterized by low water absorption capacity, and this parameter decreased as the share of walnut flour in the system increased (from 5 to 15 %). The average value of this parameter was 47.9%.…”
Section: Testing the Rheological Character Of The Semi-finished Produ...mentioning
confidence: 79%
See 1 more Smart Citation
“…A previous study has reported that the nutritional components of mealworm powder include 4.43% water, 3.5% ash, 1.17% carbohydrate, 43.5% protein, 25.3% fat, and 22.1% dietary fiber [ 8 ]. It can be inferred that the high content of fat and dietary fiber retarded the water absorption of the mixed flours [ 31 ]. Waseem et al [ 32 ] also observed a similar decrease in water absorption when wheat flour was substituted with 20% spinach powder.…”
Section: Resultsmentioning
confidence: 99%
“…Fang et al [ 32 ] reported a significantly decreased water absorption of wheat dough formulated with 10% isomaltodextrin (48.9%) compared to the control (63.0%), which is potentially attributed to the high dietary fiber content (>80%). Changes in the water absorption of flour are attributed to the presence of a large amount of fat and dietary fiber in the mixture [ 33 ]. The mealworm powder in this study contained 43.5% protein, 25.3% fat, 1.17% carbohydrate, 22.1% dietary fiber, 3.5% ash, and 4.43% water.…”
Section: Resultsmentioning
confidence: 99%